Democratic constitutional design and public policy : analysis and evidence - Congleton, Roger D.; Swedenborg, Birgitta, 1941- (MIT Press, 2006)
Leading scholars in rational choice analysis present the public choice, new institutionalist, and new political economy perspectives on the political and economic effects of constitutional design and review the accumulating empirical evidence.